The Epidemiology of Respiratory Syncytial Virus and the Impact of the COVID-19 Pandemic in a Retrospective Evaluation - Paolo Solidoro; Antonio Curtoni; Cristina Costa; Francesco Giuseppe De Rosa; Alessandro Bondi; Francesca Sidoti; Nour Shbaklo; Filippo Patrucco; Davide Favre; Elisa Zanotto; Silvia Corcione; Rocco Francesco Rinaldo (Pathogens)
Introduction: Respiratory syncytial virus (RSV) is the main etiological agent in pediatric lower respiratory tract infections. The limited availability of therapeutic options for severe clinical cases associated with RSV infection makes prophylactic interventions a priority for containment. The aim of the current study was to evaluate the epidemiology of RSV in the Piedmont population and the consequences of containment measures applied during the pandemic on viral circulation in the immediate and medium-term post-pandemic phase. Methods: This study considered all biological samples analyzed for RSV at the City of Health and Science of Turin collected from 1 January 2016 to 31 December 2023. Evaluation of the positivity rates of samples was performed and differences between pediatric and adult population swabs (nasopharyngeal, pharyngeal, nasal aspirates) and bronchoalveolar samples were reported. Results: This study analyzed 14,085 samples and highlighted a trend in Piedmont RSV infections characterized by a higher pediatric population involvement of 82% compared to the adult population at 17%. A higher number of URT infections (95%) compared to LRT infections (4.6%) was also identified. This study shows a peak in RSV cases from November to April between 2016 and 2020. Our data show no RSV positivity during the 2020/2021 winter season, a result most likely due to the influence of containment measures implemented during the COVID-19 pandemic. Conclusions: Our study provided an epidemiological panorama of RSV and its high prevalence in pediatrics and adults. Pediatrics had a higher prevalence, while adults presented a delayed trend of about one month compared to pediatrics. The effectiveness of infection control measures applied during the SARS-CoV-2 pandemic to limit viral infections were proved. Future studies may further investigate the impact of the SARS pandemic on RSV epidemiology considering patients at a higher risk of severe symptoms.